Memahami Makna Doa yang Benar dan Implikasinya dalam Kehidupan Sehari-hari Matius 7:7 - Sisga Desriman Zebua; Mega Intan Tambunan; Windi Jore Lasenov Sinamo; Jeri Hezekiel Lumbantobing; Sofia Sri Soradinah Wau; Yubilate Chriswell Zebua (Sekolah Tinggi Teologi Injili Arastamar (SETIA) Ngabang, 2024)
Many people think that prayer is a ritual carried out to ask the creator or someone they believe in. But many people also believe that prayer is not just about asking those they trust, but also that in prayer there is a form or form of giving thanks to those they trust. The writing method used is a qualitative approach. The author uses valid data sources from various books, journals, Bible Works, and the Bible. The purpose of this writing is for believers to understand prayer and live prayer in their daily lives correctly. What the author will discuss in this scientific work is how the theological study of prayer in Matthew 7:7, then how prayer is in the Greek world then how prayer is in the Old Testament, then what prayer is like in the Synagogue, then what prayer is like in the New Testament and what are the implications of true prayer in everyday life. Prayer is the breath of life for believers which must continue to be done by working and praying.